Fintech Implementation On The Financial Performance Of Rural Credit Banks - Eni Suharti; Tri Endi Ardiansyah (Jurnal Akuntansi, 2020)
This study aims to determine whether the enactment of BI regulation No.19 / 12 / PBI / 2017 by Financial Services Authority (OJK) in Indonesia has an impact on the performance of banks, especially rural banks(RCB). This’s because RCBare still bound by OJK regulations in lending with a loan mechanism requirements that are quite burdensome customers. The populationused in this study is the RCBin Banten Provincethat registered by OJKfor 2014 -2018, the sampling method used is non probability sampling, the data analysis technique uses Comparative Analysis with descriptive quantitative approach, with the help of eview .9. the results are that for the year prior to the enactment of Bank of Indonesia regulation No. 19/12 / PBI / 2017 the variable lending and capital raising has a significant negative effect on the quality of productive assets, while for theFunding variable has no effect.